2019
DOI: 10.35631/ijepc.433005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Marital Satisfaction Through Acceptance and Commitment Therapy: A Review of Marital Satisfaction Improvement of Iranian Couples

Abstract: Just about every couple considers a successful marriage a dream and aims to start spousal life, but this is an actual challenge. In reaching this aim, attaining knowledge can be a worthy initial step on the way to forming a positive and healthy marriage relationship. Acceptance and Commitment Therapy (ACT) is a new treatment with a positive impact on marital satisfaction. This form of therapy is very instrumental in bringing married couples closer and making them even more satisfied with their partners and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
1
0
1
Order By: Relevance
“…The results also showed that acceptance and commitment therapy increased the self-efficacy of the experimental group compared to the control group. These results are consistent with the findings of other studies (Rachael, 2018;Hosseini et al, 2019 andAhmadi andRaisi, 1398) that people whose acceptance and commitment therapy is effective increase their self-efficacy. To explain the results, it can be said that a large part of the skills taught in the therapy group is based on acceptance and commitment, living valuable and accepting negative emotional states, and paying attention to the person's internal states (such as emotion and cognition).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results also showed that acceptance and commitment therapy increased the self-efficacy of the experimental group compared to the control group. These results are consistent with the findings of other studies (Rachael, 2018;Hosseini et al, 2019 andAhmadi andRaisi, 1398) that people whose acceptance and commitment therapy is effective increase their self-efficacy. To explain the results, it can be said that a large part of the skills taught in the therapy group is based on acceptance and commitment, living valuable and accepting negative emotional states, and paying attention to the person's internal states (such as emotion and cognition).…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that acceptance and commitment therapy increased marital satisfaction in the experimental group compared to the control group. These results are consistent with the findings of other studies (Rachael, 2018;Hosseini et al, 2019 andAhmadi andRaisi, 1398) that individuals whose acceptance and commitment therapy is effective increase marital satisfaction. Also, in the study of Esfandiari Bayat et al (1400) in a study concluded that despite the differences in content and process of the two approaches of rational-emotive behavior therapy and therapy based on acceptance and commitment, elements such as emotional discharge, hope and universality of human experience In both treatments, it increases the forgiveness of women.…”
Section: Discussionsupporting
confidence: 92%
“…The marital adjustment and satisfaction of couples are regarded as important factors in creating a good and stable relationship ( 1 , 2 ). In fact, marital satisfaction is defined as a sense of joy and happiness of a couple in living together.…”
Section: Introductionmentioning
confidence: 99%
“…A strong mind-body connection is essential for overall well-being, as it enables individuals to respond to physical and emotional stressors more effectively. ACT promotes a holistic approach to health by integrating mindfulness and acceptance, which can enhance the mind-body connection (Hosseini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%